Diagnóstico integral de las microempresas Panadería la Adíela, Pan canela, Panadería la Integral, Tienda Oliver y Bodega Verfrut, asociadas a Cofincafé a 2013 (2014)
Colombian commercial micro-enterprises and particularly those in the Quindío Department are mostly managed by their owners, who, in spite of their high - entrepreneur profile, lack formal business administration training and rely solely on their empirical knowledge in this area. As a result of this, the functional areas of their business management present significant deficiencies. These enterprises haven't been able to develop productive processes to take over the challenges in the field and guarantee the income level needed to grow in a sustainable way, finding themselves relegated within the economic environment they belong to, and at the same time in a vulnerable condition that risks their subsistence. The focus of this research was on the diagnosis of the administrative, financial, commercial and operative areas of five micro-enterprises located in the Quindío department, devoted to the elaboration and/or commercialization of family food basket products, to identify positive and negative aspects and the current conditions each enterprise operates under in order to have enough judgment criteria to suggest them organizational improvement alternatives.